Pengaruh Penerapan Self Assesment System, E-Filling Dan E-Billing Terhadap Kepatuhan Wajib Pajak Orang Pribadi di Manggarai, Nusa Tenggara Timur - Sri Ayem; Albertus Yandi Deo (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: This study aims to investigate the impact of the implementation of self-assessment system, e-filing, and e-billing on the compliance level of individual taxpayers in Manggarai, East Nusa Tenggara. By identifying this problem, this study aims to analyze the effect of each aspect of digitalization of tax services on taxpayer compliance. This is expected to provide a better understanding of the effectiveness of digitalization in improving tax compliance at the local level Method: The research method used in this thesis is quantitative with an analytical descriptive approach. This study aims to analyze the effect of the implementation of self-assessment system, e-filing, and e-billing on individual taxpayer compliance at the Ruteng Pratama Tax Service Office, Manggarai. Primary data were collected through surveys with questionnaires distributed to randomly selected taxpayers. Data analysis was performed using descriptive statistical techniques, multiple linear regression, F test, coefficient of determination, and t test. Finding: This study explores the effect of the implementation of Self Assessment System, E-filing, and E-billing on individual taxpayer compliance in KPP Pratama Ruteng. The results of the analysis show that E-filing has a significant positive influence on tax compliance, while Self Assessment System and E-billing do not have a significant influence. These findings support the importance of technology in improving tax compliance and highlight the need for clear understanding and benefits for taxpayers regarding electronic tax technology. Novelty: This study contributes by identifying the different impacts of electronic tax systems (E-filing) on individual tax compliance, particularly in contexts that may differ from previous studies. The research highlights the importance of E-filing as an effective tool in improving tax compliance, while pointing out that other aspects such as Self Assessment System and E-billing may not have the same impact. As such, these findings provide new insights into specific factors that can influence tax compliance behavior, provide direction for further tax policy, and pave the way for further research in this field. Keywords: Self Assesment System, E-filling, E-billing, Tax Compliance